2020
DOI: 10.1007/s00068-020-01527-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical fixation and non-operative management in patients with traumatic sternum fracture

Abstract: Purpose The incidence of sternal fractures in blunt trauma patients lies between 3 and 7%. The role, timing and indications for surgical management are not well delineated and remain controversial for patients undergoing surgical stabilization of sternum fracture (SSSF). We sought to identify the national rate of SSSF in patients with a sternum fracture hypothesizing patients undergoing SSSF will have a decreased rate of mortality and complications. Methods The Trauma Quality Improvement Program (2015-2016) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…However, in a recent study, compared with nonoperative management, operative sternal fixation had a longer hospital stay, an extended ICU stay, and longer ventilator days. Meanwhile, operative fixation and nonoperative management had a similar rate of pneumonia, adult respiratory distress syndrome, unplanned intubation, and other complications [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, compared with nonoperative management, operative sternal fixation had a longer hospital stay, an extended ICU stay, and longer ventilator days. Meanwhile, operative fixation and nonoperative management had a similar rate of pneumonia, adult respiratory distress syndrome, unplanned intubation, and other complications [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined 338 patients from the Trauma Quality Improvement Program database with sternal fractures (112 in the SF group and 224 in the NOM group) that were propensity match at a ratio of 1:2 14 . In this study, the authors found an increased median ICU and hospital LOS as well as an increase in ventilator days for patients who underwent SF compared with the NOM group 14 . Furthermore, the incidence of ARDS development, pneumonia development, and unplanned intubations were similar between cohorts 14 .…”
Section: Discussionmentioning
confidence: 99%
“…They found lower mortality in the surgical group (2.7% vs. 11.2%, P=0.008) but increased median length of stay and ventilator days. There was no difference in the incidence of pulmonary complications after propensity score matching ( 49 ). Choi and colleagues ( 50 ) analyzed the 2016 National Trauma Data Bank for patients with traumatic sternal fractures after blunt trauma (n=14,760) and found surgical stabilization was performed in 1.8% of patients (n=270).…”
Section: Surgical Outcomesmentioning
confidence: 98%
“…One of the larger series from Zhao et al ( 29 ) of 64 patients with acute fracture and non-union showed decreased pain severity scores and healing in all cases, with a 6 month follow up. Christian et al ( 49 ) queried the Trauma Quality Improvement Program database for patients with sternal fractures (n=9,460) and found that 1.2% of patients underwent surgical stabilization (n=114). They found lower mortality in the surgical group (2.7% vs. 11.2%, P=0.008) but increased median length of stay and ventilator days.…”
Section: Surgical Outcomesmentioning
confidence: 99%